Analisis Film Animasi Upin Dan Ipin Dalam Menanamkan Nilai-Nilai Karakter Siswa Kelas III SD Negeri Sitimulyo 01 Pati Season 6 Episode â€œTaman Mesraâ€ - Astuti, Handika (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2020)
AbstractThis research is motivated by the number of television shows contains negative content that is often watched by school-aged children basic and upin and ipin animated film shows that contain value the characters for planting them for third grade elementary school students Country of Sitimulyo 01 Pati. This study aims to determine the value characters in Upin and Ipin season 6 television shows episode "Taman Mesra" and its effect on students of grade III SDN Sitimulyo 01 Pati. This type of research is qualitative. Collection technique The data used are: (1) Interview; (2) Questionnaire; (3) Observation; and (4) Documentation. Based on the research results obtained that data the inculcation of the character grades of class III students shows good results seen from the results of observations and questionnaires. This shows that the film upin and ipin season 6 "Garden of Intimate" can be used as a means inculcation of the character grades of class III students because in the episodesthese contain lots of good character values for emulated by children.Â Keywords: Character Value, Animated Film, Upin and Ipin